Impact of Sleep Duration on Depression and Anxiety After Acute Ischemic Stroke - Liu, Fei; Yang, Yang; Wang, Shuo; Zhang, Xiao-Li; Wang, An-Xin; Liao, Xiao-Ling; Fang, Hong-Juan; Qu, Yue; Ma, Wei-Guo; Zhang, Ning; Wang, Chun-Xue; Wang, Yong-Jun (Frontiers in Neurology, 2021)
ABSTRACT Background: Abnormal sleep duration predicts depression and anxiety. We seek to evaluate the impact of sleep duration before stroke on the occurrence of depression and anxiety at 3 months after acute ischemic stroke (AIS). Methods: Nationally representative samples from the Third China National Stroke Registry were used to examine cognition and sleep impairment after AIS (CNSR-III-ICONS). Based on baseline sleep duration before onset of stroke as measured by using the Pittsburgh Sleep Quality Index (PSQI), 1446 patients were divided into four groups: >7, 6-7, 5-6 and <5 hours of sleep. Patients were followed up with the General Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) for 3 months. Post-stroke anxiety (PSA) was defined as GAD-7 of ≥5 and post-stroke depression (PSD) as PHQ-9 of ≥5. The association of sleep duration with PSA and PSD were evaluated using multivariable logistic regression. Results: The incidences of PSA and PSD were 11.2% and 17.6% at 3 months, respectively. Compared to a sleep duration of >7 hours, 5-6 hours and <5 hours of sleep were identified as risk factors of PSA (odds ratio, OR 1.95, 95% confidence interval, CI, 1.24-3.07, P<0.01; and OR 3.41, 95% CI 1.94-6.04, P<0.01) and PSD (OR 1.47, 95% CI 1.00-2.17, P=0.04; and OR 3.05, 95% CI 1.85-5.02, P<0.01), while 6-7 hours of sleep was associated with neither PSA (OR 1.09, 95% CI 0.71-1.67, P=0.68) nor PSD (OR 0.92, 95% CI 0.64-1.30, P=0.64). In interaction analysis, the impact of sleep duration on PSA and PSD was not affected by gender (P=0.68 and P=0.29, respectively). Conclusions: Sleep duration of shorter than 6 hours was predictive of anxiety and depression after ischemic stroke.